The Steinzeitpark Dithmarschen (DE): Concept and Development of a Visitor Oriented Educational Centre for Sustainable Development - Rüdiger Kelm (EXARC Journal)
What does a Stone Age village or Stone Age house look like? (Almost) every person that we happen to randomly meet can answer this question with (subjectively recognized) certainty. Since the research of the 19th century, the knowledge people assume to have is based, not lastly, on images or ‘projections’, in psychological terminology, that, through ethnology, through the branches of archaeology that are well recognized in public media, and through the standard method of analogy from ethnological examples, are available in our cultural memory to our modern minds. These images are even somewhat encouraged these days by audience-oriented, economic interests. An important role of our museum and pedagogic work is to critically reassess and to check the validity of these images through practical experiments and trials within the framework of the model ‘Stone Age village’ at the Steinzeitpark Dithmarschen. But first, here is some basic information about the Stone Age Park in Albersdorf.